Iosif Hurko (1828-1901) : studium przypadku imperiologii stosowanej - Wiech, Stanisław (1963– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2024)
Iosif Gurko belonged to that group of tsarist state dignitaries who played a significant role in the history of Russia and the Polish nation in the second half of the nineteenth century. He actively participated in the implementation of the emancipation reform of 1861, the training of military personnel, the Russo-Turkish War of 1877–1878, the establishment of military-police rule, the development of strategic military concepts, and the creation of national, educational, and religious policies. Through these efforts, he made significant contributions during the reign of Alexander II (1881–1894) to the political, military, and cultural expansion of the Russian Empire, especially along its western frontiers. This expansion primarily hit the demographic, cultural, ethnic, and confessional potential of the Polish nation and the Catholic Church. The struggle against the ʻPolish-Latinʼ cultural area culminated in the introduction of the Orthodox Churchʼs hegemony and the Russkiy mir (Russian world) on the Polish lands. Gurkoʼs reactionary, schematic, anti-Polish in content and imperial in general character model of government born in the era of Nicholas I was confirmed by his personal wish to live to see the moment when all the joys and sorrows of Russians, to the same extent and for the same reasons, would be the joys and sorrows of Poles.
Wydanie I.
630 stron : ilustracje (w tym kolorowe) ; 25 cm.
Bibliografia, netografia na stronach 590-610. Indeks.
Zadanie sfinansowane ze środków Ministra Edukacji i Nauki RP, um. nr 2023/DPI/1917 z 18.04.2023 r., działanie nr 2
Streszczenie w języku angielskim.
Keywords: Gurko, Iosif Vladimirovich (1828-1901); governors general - Russia - biography; Russia - politics and government - 1801-1917; Kingdom of Poland (1815-1915); Poland - 1864-1918